KUALITAS BENIH TIGA AKSESI KACANG MERAH (Phaseolus vulgaris L.) PADA TIGA UMUR PANEN - , SEPTIN KRISTIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research were for knowing the effect of harvest period on red kidney bean seed quality and determine physiological maturity of three kidney bean accessions. The research has conducted in a farmerâs field in Kalangan Orchard, Sidogede Village, Grabag, Magelang Regency, Central Java and Seed Technology Laboratory, Department of Agronomy, Faculty of Agriculture, Universitas Gadjah Mada, Yogyakarta from August until December 2013. This research used 3x3 factorial and arranged in The Randomized Complete Block Design (RCBD) with three replications. The first factor were three red kidney bean accessions (Temanggung Accession, Magelang Accession, Sleman Accessions), meanwhile the second factor were three harvest periods which is 30, 35, and 40 days after flowering (daf) of 60% plant in portion of field specimen. The results of research showed that three accessions gave the same response on growth parameter, yield component, and seed quality. Physiological maturity of three accessions reached at 30 days after flowering. Delaying of harvest period up to 5 days (35 daf), even 10 days (40 daf) did not effected on seed quality (germination rate > 90%).